2023
DOI: 10.34172/jrhs.2023.104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-management Program as Adjunctive to Usual Rehabilitation Exercise on Pain and Functional Outcomes in Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Background: Home-based exercise (HBE) and patient education (EDU) have been reported as beneficial additions to usual knee osteoarthritis (KOA) rehabilitation. However, previous trials mostly examined the effects of HBE and EDU separately. Thus, this study aimed to evaluate the effects of a structured combined HBE and EDU program in addition to usual KOA rehabilitation on pain score, functional mobility, and disability level. Study Design: A parallel-group, single-blinded randomized controlled trial. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The outcome is consistent with the findings of the Ahmad et al [23], which showed that participants in the leg exercise program had a statistically significant lower level of disease severity (p<0.05) than those who had not. Additionally, findings Chuaychan et al [24] demonstrated that the self-care practices of people with knee OA considerably improved after implementation compared to before implementation (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The outcome is consistent with the findings of the Ahmad et al [23], which showed that participants in the leg exercise program had a statistically significant lower level of disease severity (p<0.05) than those who had not. Additionally, findings Chuaychan et al [24] demonstrated that the self-care practices of people with knee OA considerably improved after implementation compared to before implementation (p<0.05).…”
Section: Discussionsupporting
confidence: 91%